Implementation of Maximum Power Point Tracking on Photovoltaic Using Fuzzy Logic Algorithm - Arton Johan Lubis; Erwin Susanto; Unang Sunarya (Universitas Ahmad Dahlan, 2015)
Most energy sources that are commonly used in the world today are from fossils. This kind of energy is unrenewable and limited. Use of solar panels (Photovoltaic, PV) to generate electricity is growing fast and it can be used as an alternative energy instead of fossils. The problem faced by use of solar panels is that the generated power is not optimum for a particular load. It is always changing and influenced by the level of light (irradiance) and temperature. Therefore we need a way to maximize the power output of solar panels. Maximum Power Point Tracking (MPPT) is a method for finding its maximum power point. In this research, the MPPT is designed to locate the point of generated maximum power on solar panels. MPPT controller designed in this research is using fuzzy logic. The voltage and current from the solar panels will be fed to the fuzzy logic controller. The output of fuzzy logic in the form of a pulse width modulation (PWM) signal regulates the process of switching boost converter. Experimental results show that output power from PV increase 15.9% and the efficiency of designed boost converter ranges in approximatelly 90.97 %